Immunolocalization of anti-hsf1 to the acetabular glands of infectious schistosomes suggests a non-transcriptional function for this transcriptional activator. - Kenji Ishida; Melissa Varrecchia; Giselle M Knudsen; Emmitt R Jolly (Public Library of Science (PLoS), 2014)
Schistosomiasis is a chronically debilitating disease caused by parasitic worms of the genus Schistosoma, and it is a global problem affecting over 240 million people. Little is known about the regulatory proteins and mechanisms that control schistosome host invasion, gene expression, and development. Schistosome larvae, cercariae, are transiently free-swimming organisms and infectious to man. Cercariae penetrate human host skin directly using proteases that degrade skin connective tissue. These proteases are secreted from anucleate acetabular glands that contain many proteins, including heat shock proteins. Heat shock transcription factors are strongly conserved activators that play crucial roles in the maintenance of cell homeostasis by transcriptionally regulating heat shock protein expression. In this study, we clone and characterize the schistosome Heat shock factor 1 gene (SmHSF1). We verify its ability to activate transcription using a modified yeast one-hybrid system, and we show that it can bind to the heat shock binding element (HSE) consensus DNA sequence. Our quantitative RT-PCR analysis shows that SmHSF1 is expressed throughout several life-cycle stages from sporocyst to adult worm. Interestingly, using immunohistochemistry, a polyclonal antibody raised against an Hsf1-peptide demonstrates a novel localization for this conserved, stress-modulating activator. Our analysis suggests that schistosome Heat shock factor 1 may be localized to the acetabular glands of infective cercariae.